Pelaksanaan Standar Pengelolaan Perpustakaan Di UPT SMK Musi Banyuasin - Asep Rohman; Ivan Riyadi; Mail Hilian Batin; Afif Alfiyanto (Studia Manageria, 2022)
The purpose of this study is to determine whether this library has met the standards of library management and whether there are supporting and inhibiting factors in implementing library management standards in the school. This research is a type of qualitative research with a descriptive approach. Data collection techniques used are observation, interviews and documentation. The techniques used in data analysis are data reduction, data presentation and conclusion drawing. While the sources of information in this research are the Head of the Library, the Principal and 3 Librarians. The results of this study indicate that; 1) Planning of work programs in library management at UPT SMK Negeri 14 Musi Banyuasin is carried out by 1) compiling a work program; 2) the organization of the library is carried out through coordination with the head of the library as the coordinator in forming the organizational structure and assisted by 3 staff on duty; 3) Implementation of work programs in library management as planned at the planning stage; 4) the library supervises every day, reports on its library activities within a period of 6 months. And evaluation is done at the end of each semester.